Assessing the Influence of Social Media Advertising on Purchase Intentions among Restaurant Consumers in Kathmandu - Paudel, Shubhanjan; Adhikari, Prem Raj (Journal of Business and Social Sciences Research, 2025)
Social media have been a boon and an X-factor way of promotion among today’s generation. It has been able to not only connect the current generation (Gen Z) to the world but has also created those linkages between the past and the present. With more Nepalese having internet access in their hands, the knowledge base has increased along with access to information and has hence impacted the decision-making phenomenon of individuals. The study used five independent variables that make up the social media advertisements: aesthetics, content, price incentive, emotional drive and celebrity presence in front of Consumer Purchase Intention (dependent variable). The relationship between these two entities were further put to the test with three moderating variables to the relationsin the form of social media usage rate, income level and gender to check the impact.